Digital devices to assess vaccine hesitancy and promote pertussis vaccination during pregnancy. (20th October 2021) - Arzilli, G; Scardina, G; Menicagli, D; Lucaccini, E; Sironi, D; Papini, F; Tavoschi, L; Lopalco, PL; Privitera, G
Abstract: Introduction: Vaccination against pertussis in pregnancy is the main strategy to prevent the disease in the first trimester of life of new-borns. Effective communication is essential to successfully engage pregnant women. The use of digital devices within the outpatient setting may be helpful to engage patients before and during the consultation. The aim of this study was to develop and test an e-health tool to assess vaccine hesitancy and to deliver tailored information and education interventions to raise awareness and promote vaccine acceptance. Methods: One-hundred-and-five participants were recruited in 4 ob-gyn clinics. Participants were invited to complete a self-administered psychometric questionnaire to assess vaccine hesitancy, disease beliefs and self-efficacy perception on health behaviours on a tablet. Participants were randomly allocated to three communication-format types providing equivalent content: 1)a single video simulating a patient-doctor conversation on the topic; 2)an interactive platform with five infographics videos; 3)a paper leaflet followed by a brief consultation with the physician. The intention to get vaccinated during pregnancy was assessed through a specific question before and after the intervention. Results: In the pre-intervention phase there was no difference observed between groups in terms of the variable "intention" to get vaccinated. After the intervention, participants of groups 1 and 3 showed a higher intention to get vaccinated than group 2 at the Kruskal-Wallis test (H(2)=6.008, p < 0.05). Post-intervention intention to vaccinate correlated with Individual Self-Efficacy (rs(105)=0.30, p < 0.001) and was inversely associated with vaccine hesitancy (rs(105)=0.34, p < 0.001). Conclusions: We implemented and assessed the impact of different communication strategies to promote vaccine uptake among pregnant women. Our results suggest comparable effect may be obtained using simulated versus live patient-physician communication. Key messages: The use of digital devices allows an effective and manageable communication about vaccination to pregnant women. In the present study, the implementation of digital forms of communication allowed a comparison with standard procedures of information towards vaccination, demonstrating their equivalence.